Impact of Organic Micropollutants Causing Mass Mortality of the Clams (Mactra aequisulcata) Due to Charactersitic Distribution at Karachi Coast, Pakistan: Micropollutants of the Clams (Mactra aequisulcata) - Khanam, Safia; Munshi, Alia Bano; Ahsan, Hina; Begum, Razia (Biological Sciences - PJSIR, 2020)
Mass mortality of bivalve clams along with some other marine fauna was observed during the month of May 2016, mainly consisting of the clams (Mactra aequisulcata) of family Veneridae surfaced over the Clifton coast. The occurrence of mass mortality of the venerid clams Mactra aequisulcata and other marine life has been studied due to the toxicity of chlorinated hydrocarbons (DDTs, HCHs, hexa chloro benzene (HCB), chlordane, dieldrin (4-chlorophenyl), methanol (TCPMOH) and heptachlor epoxide and polychlorinated biphenyls (PCBs). Significant compositional characteristics of PCBs and DDTs were found in all dead clams and other fauna including fish (Johnius carutta), crabs (Portunus pelagicus), gastropods (Babylonia spirata), bivalves (Anadara antiquata), (Mactra aequisulcata) and the pen shell (Atrina pectinata) from Karachi coast, Pakistan. Mean concentrations (ranges) of organochlorine pesticides (OCPs) in crab (Portunus pelagicus) and fish samples were 1.1 (<0.01-1.5), 0.22 (<0.01-1.1) and 0.14 (<0.01-1.3) /µg/g. Those in, bivalves (Anadara antiquata) and pen shell (Atrina pectinata), clams (Mactra aequisulcata) were 0.09 (<0.02-1.2), 0.22 (<0.02-1.3) /µg and 0.13 (<0.01-0.27), respectively. The heptachlor epoxide was found in highest concentration in clam samples (25.00 ± 30.92) µg/g, (wet weight) however, in bivalves, (2.30 µg/g, (wet weight), which were higher than those in other gastropods. Polychlorinated biphenyls (PCBs) concentrations were also measured in the same samples of gastropods (Babylonia spirata), fish (Johnius carutta), crab (Portunus pelagicus), clams (Mactra aequisulcata), bivalves (Anadara antiquata) and the pen shell (Atrina pectinata) to determine the possible cause of mass mortality. The DDT to metabolites (DDD & DDE) concentration ratios exceeded upto 1.0 in the sessile fauna that is clams (Mactra aequisulcata) and the pen shell (Atrina pectinata) from Karachi coast. These organisms also exhibited dichloro diphenyl trichloroethane (DDT) inputs, whereas dichloro diphenyl trichloroethane (DDD) was found to be in degraded component and PCBs were generally in low concentrations. The concentrations of DDTs were higher than the ERL guidelines in the coastal areas of Karachi, suggesting that there is potential of ecological risk present in the prevailing environment.